1990
DOI: 10.1073/pnas.87.11.4115
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil cytoplasmic autoantibodies induce neutrophils to degranulate and produce oxygen radicals in vitro.

Abstract: Anti-neutrophil cytoplasmic autoantibodies (ANCA) are in the circulation of most patients with pauciimmune necrotizing vasculitis and pauci-immune crescentic glomerulonephritis. The current study demonstrates an effect of these autoantibodies on neutrophil function in vitro. ANCA cause normal human neutrophils to undergo an oxidative burst and degranulate. Both ANCA phenotypes (i.e., cytoplasmicpattern ANCA and myeloperoxidase-specific ANCA) induce neutrophil activation. ANCA sera and purified immunoglobulins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
737
1
22

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,161 publications
(775 citation statements)
references
References 34 publications
15
737
1
22
Order By: Relevance
“…In this assay, wells coated with PR3 (Bio Advance) were first treated with 100 l of 20 mM freshly prepared periodic acid (HIO 4 ; SigmaAldrich) at 4°C for 30 minutes, in order to prevent nonspecific binding of lectins to carbohydrate determinants on PR3. Desialylation of PR3 does not affect the binding of anti-PR3 antibodies, since the levels of anti-PR3 antibodies determined on HIO 4 -treated PR3 were strongly and significantly correlated with the levels of anti-PR3 antibodies determined on native PR3. After 2 washes with 300 l of sample buffer (Bio Advance), 100 l of each human serum, diluted 1:50, was added in duplicate and incubated for 60 minutes at 37°C.…”
Section: Methodsmentioning
confidence: 90%
“…In this assay, wells coated with PR3 (Bio Advance) were first treated with 100 l of 20 mM freshly prepared periodic acid (HIO 4 ; SigmaAldrich) at 4°C for 30 minutes, in order to prevent nonspecific binding of lectins to carbohydrate determinants on PR3. Desialylation of PR3 does not affect the binding of anti-PR3 antibodies, since the levels of anti-PR3 antibodies determined on HIO 4 -treated PR3 were strongly and significantly correlated with the levels of anti-PR3 antibodies determined on native PR3. After 2 washes with 300 l of sample buffer (Bio Advance), 100 l of each human serum, diluted 1:50, was added in duplicate and incubated for 60 minutes at 37°C.…”
Section: Methodsmentioning
confidence: 90%
“…Possibly, these autoantibodies are simply an epiphenomenon of chronic inflammation. Falk et a1 (42), however, showed that ANCA recognizing PR3 and MPO can induce the respiratory burst and degranulation of primed neutrophils in vitro. Initial studies in our laboratory have shown that anti-LF antibodies from RA patients are also capable of inducing activation of primed granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…pathogenesis of ANCA.associated vasculitis and could be used as a marker for disease activity [8]. In vitro, ANCA can activate neutrophils to produce reactive oxygen species, degranulate and damage target cells [9]. Standardized indirect immunofluorescence tests to diagnose and monitor patients have been developed, based on the typical cytoplasmic pattern (cANCA) of alcohol-fixed neutrophils using patient's sera.…”
Section: Introductionmentioning
confidence: 99%